Language in international business : developing a field - Brannen, Mary Yoko; Mughan, Terry (Palgrave Macmillan, 2017)
Tracing the treatment of language in international business as represented in the Journal of International Business Studies, this seminal collection critically explores the conceptualizations of language that have been adopted or ignored by international business scholars over the years and showcases nine articles that have played an important role in establishing and advancing the field. In today's increasingly globalized context of business, significantly richer theories from interdisciplinary perspectives are needed to explain the complexity of the interplay between multiple facets of language and how they affect day-to-day operations. With insights from linguistics, psychology and organizational theory, Language in International Business provides an assessment of scholarly efforts to uncover the profound impact that language has on global business today and proposes some important ways in which this nascent field of language in international business may be further advanced. Chapter 9 is licensed under a Creative Commons Attributtion NonCommercial-NoDerivs 3.0 Unported License. The Journal of International Business Studies (JIBS) is an official publication of the Academy of International Business and is the top-ranked journal in the field of international business. The goal of JIBS is to publish insightful, innovative and impactful research on international business. JIBS is multidisciplinary in scope and interdisciplinary in content and methodology. For more information, visit www.jibs.net. The Academy of International Business (AIB) is the leading association of scholars and specialists in the field of international business. A global community of scholars and researchers for the creation and dissemination of knowledge about international business and policy issues, the AIB transcends the boundaries of single academic disciplines and managerial functions to enhance business education and practice. For more information, visit aib.msu.edu.
Keywords: International business enterprises.; International trade.; elektronické knihy; electronic books